Der Prozess Jesu - aus römisch-rechtlicher Perspektive - Paulus, Christoph G. 1952- (Schriftenreihe der Juristischen Gesellschaft zu Berlin, 2016)
Although it is clear that the trial of Jesus has been extensively discussed and described before, new aspects are revealed by a strict focus on the written text from the perspective of legal history. The author follows this approach and comes to the inexorable conclusion that Jesus’s sentence was fully consistent with the terms of Roman penal and procedural law. - Auch wenn das Thema - naturgemäß - bereits viel diskutiert und beschrieben worden ist, eröffnen sich doch neue Aspekte, wenn man mit strikter Konzentration auf eine rechtshistorische Betrachtungsweise den geschriebenen Text analysiert. Gena